2018
DOI: 10.1038/s41429-018-0060-0
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a jadomycin incorporating l-ornithine, analysis of antimicrobial activity and jadomycin reactive oxygen species (ROS) generation in MDA-MB-231 breast cancer cells

Abstract: Herein, we report the characterization and antimicrobial activity of a previously unreported jadomycin (1) obtained from a culture of S. venezuelae ISP5230 with L-ornithine (Orn). 1 arises from the rearrangement of a putative five-membered ring containing jadomycin incorporating Orn, whereby intramolecular attack of the E-ring carbonyl from the δ-NH group of the Orn side chain results in collapse of the oxazolone ring and formation of a stable six-membered lactam. This rearrangement produces a jadomycin with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…In vivo and vitro evidence suggests that ornithine and its related metabolic products, including ammonia and polyamine, play a role in cancer cell activity as well as tumor development 5 , 10 12 . However, it is unknown whether ornithine is associated with breast cancer development in humans.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo and vitro evidence suggests that ornithine and its related metabolic products, including ammonia and polyamine, play a role in cancer cell activity as well as tumor development 5 , 10 12 . However, it is unknown whether ornithine is associated with breast cancer development in humans.…”
Section: Introductionmentioning
confidence: 99%
“…The groups of Jakeman and Rohr have harnessed the reactivity of intermediate 49 to incorporate a slew of amino acids, whose common primary amine serves as a potent nucleophile. For these reactions, amines that lack the spatial proximity of a carboxylic acid found in amino acids would hypothetically not result in the cycloaddition of the full jadomycins. While experiments such as these would further support the nonenzymatic mechanism, they have not been performed.…”
Section: Categories Of Nonenzymatic Mechanismsmentioning
confidence: 57%
“… This is a rarity in nonenzymatic biosynthesis, where it is more common for these nonenzymatic transformations to occur on fully matured natural products or those that no longer require enzymatic involvement. Furthermore, aglycone jadomycins produced naturally or unnaturally do not retain the same level of bactericidal activity as other jadomycin analogues. ,, This suggests that the nonenzymatic incorporation of amino acids, which is necessary for said glycosylation, is required for environmental fitness.…”
Section: Categories Of Nonenzymatic Mechanismsmentioning
confidence: 99%
“…For example, a recent study indicated that jadomycin Orn may induce more ROS production and be more efficacious than jadomycin B. 59 Additional mechanisms such as the possibility of the Prx/Trx and GST/GPx antioxidant systems primarily reducing jadomycin‐induced H 2 O 2 have been proposed, but not yet explored. 8 While in vitro cell experiments are ideal for identifying initial evidence of cytotoxicity and mechanistic details, in vivo animal models are needed to observe and predict additional medical benefits, toxicities, and adverse effects.…”
Section: Limitations and Future Directions For Jadomycin Breast Cancer Cell Cytotoxicity Studiesmentioning
confidence: 99%
“…Ideally, we should also broaden our knowledge of less‐studied jadomycins, and explore other pathways that involve jadomycins. For example, a recent study indicated that jadomycin Orn may induce more ROS production and be more efficacious than jadomycin B 59 . Additional mechanisms such as the possibility of the Prx/Trx and GST/GPx antioxidant systems primarily reducing jadomycin‐induced H 2 O 2 have been proposed, but not yet explored 8 .…”
Section: Limitations and Future Directions For Jadomycin Breast Cancer Cell Cytotoxicity Studiesmentioning
confidence: 99%